Cooperative Principle and its Maxims of Comments in Text Your Say of The Jakarta Post - Sulton, Ahmad Fauzi (JEELS (Journal of English Education and Linguistics Studies), 2014)
This study aims to find what maxims and how the maxims are observed or infringed in text your sayof The Jakarta Post based on the cooperative principle and maxims. The research design of this study is descriptive qualitative. The resercher himself is the main instrument. He uses typological analysis (based on categories). In addition, investigator triangulation is usedtovalidate the analysis. The research results show that all maxims are observed and infringed. In this case, the most comments (42 comments from 53) gathered in 'text your say' of The Jakarta Post do not match the cooperative principle and they also infringe and observe one or some of the maxims.